The evaluation of TVET Instructor’s training needs analysis using curriculum development based on vocational ability structure in Malaysia / Wan Ahmad Jailani Wan Ngah, Norlida Buniyamin and Sharida Mohd. Sharif - Wan Ngah, Wan Ahmad Jailani; Buniyamin, Norlida; Mohd. Sharif, Sharida (Universiti Teknologi MARA, 2021)
This paper aims to evaluate the use of a method called Curriculum Development Based on Ability Structure (CUDBAS) in evaluation TVET Instructor’s Training Needs Analysis. This method profiles each instructor into a structured measurement based on ability of work. The results from the measurements are analysed systematically with the goal to reduce the competency gap among the instructors and simultaneously identify experts within this group to be fully utilized across agencies and ministries in Malaysia. As a result, training can be planned and implemented effectively with cost saving by matching trainer and trainee into a single system toward the right trainer, right training and right time. An online survey was conducted to evaluate user’s satisfaction level of using the system from multiple public agencies those currently using the method. The result of the survey is analysed in order to explain the influence of the identified factors that lead to user’s satisfaction. The ouput of the result may cause implement of TNA (Training Need Analysis) using CUDBAS to be be more widely use within public agencies in Malaysia.